Study protocol: A randomized controlled trial of chemoradiotherapy versus chemotherapy as neoadjuvant therapy for resectable pancreatic cancer (CSGO-HBP-027) - Yoshito Tomimaru; Hirofumi Akita; Keisuke Tamari; Sakae Maeda; Hiroshi Wada; Yoshifumi Iwagami; Chikato Koga; Naoki Hama; Akira Tomokuni; Shogo Kobayashi; Tadafumi Asaoka; Masanori Tsujie; et al. (PLoS ONE, 2026)
Despite advances in multimodal treatment, the long-term survival of patients with resectable pancreatic ductal adenocarcinoma (PDAC) remains poor. In Japan, neoadjuvant chemotherapy with gemcitabine and S-1 (GS) has demonstrated a survival benefit compared with upfront surgery. The addition of radiotherapy to chemotherapy may further improve outcomes by enhancing local tumor control and increasing R0 resection rates; however, no randomized trial has directly compared GS alone with GS plus radiotherapy (GS-RT) in patients with resectable PDAC. The CSGO-HBP-027 trial is a multicenter, randomized phase II/III study designed to evaluate whether neoadjuvant GS-RT improves survival compared with GS alone. This trial will enroll 200 patients with resectable PDAC, who will be randomized in a 1:1 ratio to receive either two cycles of GS or two cycles of GS with concurrent radiotherapy (50.4 Gy in 28 fractions), followed by surgery scheduled 3–8 weeks after completion of neoadjuvant therapy. The primary endpoint is overall survival, and secondary endpoints include resection rate, R0 resection rate, histological tumor response, progression-free survival, and safety. Overall survival will be compared between the two treatment arms using the stratified log-rank test, with adjusted hazard ratios estimated using the Cox proportional hazards model. This trial was registered with the Japan Registry of Clinical Trials (jRCTs051250150). The CSGO-HBP-027 trial will provide evidence on whether neoadjuvant GS-RT improves survival in patients with resectable PDAC compared with GS alone. The results of this study are expected to clarify the optimal neoadjuvant treatment strategy for resectable PDAC and to provide high-quality evidence regarding the clinical value of adding radiotherapy to GS-based neoadjuvant therapy.